Amplifying Feminism through the Empowerment Program Kartini Corner: A Gender Mainstreaming Endeavour in Rural Indonesia - Listiani, Herlina Dedy; Sukesi, Keppi; Wike, Wike (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2025)
Limited access and a strong patriarchal culture in rural Indonesia remain efficacious factors that limit women's choices and participation in the public domain. The reality of gender injustice many women experience has been at the heart of feminist struggles since the 19th century. With a qualitative approach, this study aims to identify and analyze feminist values implemented by the